Effects of Reciproc, ProTaper Next and WaveOne Gold on Root Canal Walls: A Stereomicroscope Analysis - Cassimiro, Marcely; Romeiro, Kaline; Gominho, Luciana; de Almeida, Andressa; Belo, LÃvia; Albuquerque, Diana (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to analyse the potential occurrence of dentinal defects after root canal preparation using three engine-driven instruments. Methods and Materials: Eighty permanent mandibular incisors were selected. Twenty teeth did not undergo preparation, and the remaining teeth were divided into three groups (n=20): Reciproc (REC), ProTaper Next (PTN) and WaveOne Gold (WOG). The samples were dyed with methylene blue, sectioned perpendicularly to the long axis in 3-, 6- and 9-mm slices and were finally observed under a stereomicroscope (under 25×). The absence/presence of dentinal defects was documented by two blind observers. The data were analysed using Pearson’s chi-squared test with a confidence level of 95% (P=0.05). The time to prepare the samples was recorded, and the groups were compared using F-test (ANOVA). Results: The control group did not present any defects, and the differences between the control and experimental groups were statistically significant (P<0.05). WOG, PTN and REC caused microcracks on 60%, 33.33% and 18.33% of the samples, respectively. No significant differences between the groups in the 3-mm sections (P=0.126) were observed. There were significant differences in the 6-mm (P=0.042) and 9-mm sections (P<0.001). When WOG and PTN were used to perform root canal preparation, a significant difference was found in the average time (P=0.047). Conclusion: All the used instruments caused dentinal defects in the root dentin. All the instruments were used to perform the preparation with a similar average time. Keywords: Dentinal Defects; Microcracks; Nickel-Titanium Instruments; Root Canal Preparation